Experimental investigations of wall jet droplet impact on spray impingement fuel film formation. (1st April 2019) - Pan, Hujie; Xiao, Di; Hung, David; Xu, Min; Li, Xuesong
Highlights: Different regimes of spray impingement process were revealed and analyzed. The droplet with high horizontal velocity would glide away from the plate. A preliminary criterion corresponding to the new "glide" regime was derived. Abstract: The understanding of fuel spray impingement phenomenon and its impact of film formation on wall are significant for engine related applications, such as emission reduction and lubrication improvement, etc. However, the impingement phenomenon of the airborne droplets in the wall jet moving parallel to the wall has not been fully understood yet, especially for the fact that negligible amount of fuel film is formed underneath the wall jet. In this experimental research, various laser diagnostic techniques, including laser-induced fluorescence, Mie scattering, phase Doppler interferometry, and particle imaging velocimetry were utilized to capture both macroscopic and microscopic behavior of the spray impingement process. It was found that droplets in the spray with a high tangential velocity may be governed by the lift force induced by the boundary layer near the plate, gliding away without impinging the wall and forming wall film. Based on the observations, a modified impingement criterion is proposed to incorporate such gliding effects to improve the current understanding of droplet-wall interactions.